2012
DOI: 10.2478/s11658-012-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential fucosyltransferase IV expression in squamous carcinoma cells is regulated by promoter methylation

Abstract: Enhanced fucosyltransferase IV (FUT4) expression correlates with increased tumor malignancy in many carcinomas. However, little is known about the regulation of FUT4 expression, and whether FUT4 expression is influenced by the methylation status of the FUT4 promoter is unclear. In this study, we demonstrated that FUT4 expression is negatively correlated with the methylation degree of a CpG island in the FUT4 promoter, suggesting that the methylation status of FUT4 promoter regulates the expression of FUT4. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Increased FUT4 expression has been reported in many cancers, such as gastric, colorectal, and lung cancer (18–20). Our previous study showed that high proliferative ability skin cancer A431 cells carried a higher level of FUT4 than low proliferative capability SCC12 cells (21). Moreover, high expression of FUT4 promoted cell proliferation by augmenting the synthesis of LeY (22), while suppressing the expression of FUT4 by RNAi technology reduced the synthesis of LeY and inhibited cell growth (9).…”
Section: Introductionmentioning
confidence: 99%
“…Increased FUT4 expression has been reported in many cancers, such as gastric, colorectal, and lung cancer (18–20). Our previous study showed that high proliferative ability skin cancer A431 cells carried a higher level of FUT4 than low proliferative capability SCC12 cells (21). Moreover, high expression of FUT4 promoted cell proliferation by augmenting the synthesis of LeY (22), while suppressing the expression of FUT4 by RNAi technology reduced the synthesis of LeY and inhibited cell growth (9).…”
Section: Introductionmentioning
confidence: 99%
“…FUT4 expression is increased in various tumor cells (Julien et al, 2011;Padro et al, 2011;Li et al, 2012) and regulated by promoter methylation (Li et al, 2012). In breast cancer cells, FUT4 induced activation of phosphatidylinositol 3 kinase (PI3K)/AKT, and inactivation of glycogen synthase kinase 3 beta (GSK3b) and nuclear translocation of nuclear factor of kappa light polypeptide gene enhancer in B-cells (NF-lB), resulting in increased Snail and MMP-9 expression and greater cell mobility (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Of the fucosyltransferases involved in the biosynthesis of Lewis type antigens, the methylation of FUT4 promoter has been reported to be inversely correlated with gene overexpression and tumor invasion [ 84 ]. In breast cancer cells, FUT4 overexpression, due to down-regulation of miR-224-3p, is associated with chemoresistance [ 85 ], while its inhibition by miR-493-5p attenuates invasiveness and tumorigenicity [ 86 ].…”
Section: Epigenetic-regulation Of Cancer Associated Structuresmentioning
confidence: 99%